2017
DOI: 10.1093/cvr/cvx167
|View full text |Cite
|
Sign up to set email alerts
|

Triggered intracellular calcium waves in dog and human left atrial myocytes from normal and failing hearts

Abstract: TCWs develop during the atrial AP and thus could affect AP duration, producing repolarization gradients and creating a substrate for reentry, particularly in HF where they develop at slower rates and a higher incidence. TCWs may represent a mechanism for the initiation of atrial fibrillation particularly in HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
3
19
0
1
Order By: Relevance
“…Voigt et al showed that CaMKII-p-RyR2 (S2814) leads to an increased propensity for spontaneous Ca 2+ release (Ca 2+ waves) -and consequent delayed afterdepolarizations -in atrial myocytes from patients with chronic AF (16). Very recently, we have shown that atrial myocytes demonstrate a propensity for Ca 2+ waves that occur in the setting of rapid heart rates (17). These TCWs occur during atrial systole and cause membrane depolarizations that are conducive to the genesis of early-afterdepolarizations (30).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Voigt et al showed that CaMKII-p-RyR2 (S2814) leads to an increased propensity for spontaneous Ca 2+ release (Ca 2+ waves) -and consequent delayed afterdepolarizations -in atrial myocytes from patients with chronic AF (16). Very recently, we have shown that atrial myocytes demonstrate a propensity for Ca 2+ waves that occur in the setting of rapid heart rates (17). These TCWs occur during atrial systole and cause membrane depolarizations that are conducive to the genesis of early-afterdepolarizations (30).…”
Section: Discussionmentioning
confidence: 81%
“…Preliminary data indicate that these TCWs cause incomplete cellular repolarization on a beat-to-beat basis and, therefore, could contribute to afterdepolarizations and/or dispersion of repolarization (30). The incidence of TCWs increases significantly in HF myocytes, with Ca 2+ waves occurring at significantly longer cycle lengths than in normal myocytes (17). Since CaMKII-p-RyR2 (S2814) has been shown to alter SR Ca 2+ release (16), and as Ox-CaMKII -which is known to be enzymatically active in the absence of Ca 2 + / CaM -was increased in the HF PLA, we measured the level of CaMKII-p-RyR2 (S2814).…”
Section: Increased Incidence Of Tcws In Hf Pla Myocytes and Attenuatimentioning
confidence: 93%
See 1 more Smart Citation
“…These results demonstrate that sympathetic stimulation promotes an increased frequency of subcellular Ca 2+ waves that propagate inside the cell interior. These subcellular Ca 2+ waves have been studied extensively by our group (21,22) and have been shown to occur in normal atrial myocytes under rapid pacing conditions. In both cases, these waves originate under conditions of increased sarcoplasmic reticulum (SR) loading, where the interior of the atrial myocyte is sensitized and can support the propagation of Ca 2+ waves.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing SR calcium content is generally pro-arrhythmic as this can lead to an increased frequency of delayed afterdepolarizations, and this is often seen in the atria of those with heart failure (Yeh et al, 2008 ; Hohendanner et al, 2015 , 2016 ; Aistrup et al, 2017 ). While in rodents a decrease in SR calcium content (Saba et al, 2005 ) is associated with reduced SERCA, PLB, and sarcolipin expression (Shanmugam et al, 2011 ), a somewhat different story predominates in large mammals in which atrial SR calcium content increases in heart failure (Yeh et al, 2008 ; Clarke et al, 2015 ; Aistrup et al, 2017 ) despite decreased calcium reuptake by SERCA (Clarke et al, 2015 ; Hohendanner et al, 2016 ). This apparently paradoxical finding has been explained by the decrease in atrial I Ca(L) where inhibiting I Ca(L) in control cells reproduces the increase in SR calcium content.…”
Section: The Interplay Between Heart Failure and Atrial Fibrillationmentioning
confidence: 99%